2020
DOI: 10.30534/ijatcse/2020/154952020
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of web platforms of learning management systems for distance education in the face of social isolation

Abstract: Education is one of the sectors that were affected by the Covid-19 pandemic that forced citizens to keep us isolated in our homes, however, education had to adapt to circumstances and as a result Online Classes were implemented. in the different educational centers for which it is necessary to know the best online learning system to be able to implement in the institutions. In this work, a work methodology based on Analytic Hierarchy Process (AHP) was applied to be able to compare the different LMS shown in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…By June 30, 2020, air pollution in the two stations, in terms of PM10, PM2.5 and NO2 and CO2, had decreased (Table XIII), it is observed that there was an improvement in air quality in the station of CAR, being the index of good air quality, while in the VMT station it remains moderate. Likewise, compared to the historical period (the previous two years 2018-2019), it is show that the air quality index in the VMT and CAR stations is moderate [11].…”
Section: B Discussion About Results On the Case Studymentioning
confidence: 87%
See 1 more Smart Citation
“…By June 30, 2020, air pollution in the two stations, in terms of PM10, PM2.5 and NO2 and CO2, had decreased (Table XIII), it is observed that there was an improvement in air quality in the station of CAR, being the index of good air quality, while in the VMT station it remains moderate. Likewise, compared to the historical period (the previous two years 2018-2019), it is show that the air quality index in the VMT and CAR stations is moderate [11].…”
Section: B Discussion About Results On the Case Studymentioning
confidence: 87%
“…3) The degree of divergence of the intrinsic information in each criterion is calculated using (10). (10) 4) In the weight entropy 𝑤 of each criterion , we have to use (11). for each sampling station , with respect to the grey classes , is calculated using (12).…”
Section: ∑ (7)mentioning
confidence: 99%
“…It reinforces the need for social interaction and, as the pandemic has shown, sharing a time and place affords an ease of interpersonal connection that does not have an online equivalent. This does not mean of course that interpersonal connections cannot or should not be fostered online, and many learning management systems do provide such functionalities (Delgado et al, 2020). However, this study raises some considerations around how formal and informal online relationships intersect.…”
Section: Discussionmentioning
confidence: 93%